Cultural perspectives on farmers' perceptions Mennonite-non-Mennonite farmers in Southwestern Ontario - Macintosh, Pamela J. (Department of Humanities, Nova Scotia Agricultural College and Rural Research Centre, 1993)
An exploration of cultural differences between two types of farm communities--Mennonites and Non-Mennonites-- in Southwestern Ontario, with focus on quality of life satisfaction, community satisfaction, and community environment. A brief discussion of previous research on the subject precedes the study reported here. The study is based on a random sample of 82 respondent farmers. Analysis reveal some notable differences between Mennonite and Non-mennonite farmers. The Mennonites consistently show a stronger attachment to their community, accountable by a strong cultural identity through their religious base. Both sample group display average to high levels of satisfaction with the quality of their lives, although Mennonite farmers exhibit consistently higher levels